Pesquisa-ação na formação continuada de professora de língua portuguesa: ressignificação da prática e da visão sobre os alunos - Oliveira, Raquel Gonçalves de (Universidade do Vale do Rio dos Sinos, 2019)
The present study is based on literacy development of a Portuguese Language teacher when she proposed to create a project for teaching public oral genre on the senior year of high school from a public school in the country side of Minas Gerais. For that matter, it was attempted to comprehend all research-action movements that the Portuguese Language teacher does in order to re-signify her practice and how impact on students work. Therefore, she developed a educational project with focus on oral presentation genre production. In order to achieve this general goal, it was centered on these specific goals: understand how a high school senior class student transposes text content from written form to oral form, during preparation and discursive practice of oral presentation genre, and opportunize learners development of oral proficiency on a public sphere of oral genre productions, so that the learner can know the genre characteristics and make monitored use of the language to achieve his presentation goal in contact with audience. The Research is qualitative-interpretative and it is characterized by research-action, considering the teacher is also a researcher. It anchors itself on teachers' literacy concepts proposed by Kleiman (2008), orality by Dolz and Schneuwly (2004), Rojo and Schneuwly (2006), and Marcuschi (1997), and on digital literacy by Zammit (2012), Kersch and Marques (2017). Research data revealed that the Portuguese teacher, by developing literacy at her workplace, resignified not only her teaching practices, but also her profession well-being. Transformed practice was based on work methodology with projects in Portuguese Classes of High School, with PDG characteristics (KERSCH, GUIMARÃES, 2012), allowing students to develop oral proficiency through oral genre presentation production and even master genre characteristics. Results point in the direction of new possible researches on how to teach students to research - and report - and realise the necessity to respect authorship.
Keywords: Multiletramentos; Letramento do professor; Projeto didático; Gêneros orais; Exposição oral; Multiliteracy; Teacher's Literacy; Teaching projects; Oral genres; Oral presentation; ACCNPQ::Lingüística, Letras e Artes::Lingüística